2022
DOI: 10.53964/ijams.2022002
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Versus Inverse Optimum Safety Factor Approaches for Reliability-based Topology Optimization

Abstract: Objective:The purpose of this study is to develop new reliability-based topology optimization (RBTO) approaches in order to develop new topology layouts, which will improve the structure rigidity and improve reliability levels as compared to previous RBTO layouts (or approaches).Methods: There are two ways in which deterministic topology optimization problems can be categorized: objective-based approach (OBA) and performance-based approach (PBA). The RBTO problems consist of performing the OBA and PBA under re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…The developed RBTO approaches in this work allow to control the resulting topologies considering the different used functions (objective and constraints). When comparing the different findings in this work with to our previous one [32], the resulting reliabilitybased topologies here have higher rigidity and less material quantity in certain cases, which can be considered as a new advantage of the use of RBTO approaches. In addition, a sensitivity study in [32] showed a big influence of the geometrical parameters on the structural compliance (rigidity) for the used 2D bicycle frame structure.…”
Section: Future Work and Perspectives For Rbto Approachessupporting
confidence: 50%
See 1 more Smart Citation
“…The developed RBTO approaches in this work allow to control the resulting topologies considering the different used functions (objective and constraints). When comparing the different findings in this work with to our previous one [32], the resulting reliabilitybased topologies here have higher rigidity and less material quantity in certain cases, which can be considered as a new advantage of the use of RBTO approaches. In addition, a sensitivity study in [32] showed a big influence of the geometrical parameters on the structural compliance (rigidity) for the used 2D bicycle frame structure.…”
Section: Future Work and Perspectives For Rbto Approachessupporting
confidence: 50%
“…When comparing the different findings in this work with to our previous one [32], the resulting reliabilitybased topologies here have higher rigidity and less material quantity in certain cases, which can be considered as a new advantage of the use of RBTO approaches. In addition, a sensitivity study in [32] showed a big influence of the geometrical parameters on the structural compliance (rigidity) for the used 2D bicycle frame structure. So, the geometry uncertainty of hip stems should be included to study the possibility of providing different layouts with a significant difference.…”
Section: Future Work and Perspectives For Rbto Approachessupporting
confidence: 50%